A. To create a linear function g(x) such that f(x) = g(x) has exactly one solution, we need to make sure that f(x) and g(x) do not intersect. This means that the slopes of the two functions must be different. Let's choose a different slope for g(x).
Let g(x) = -3x + 2.
B. To find the exact solution to f(x) = g(x), we set the two functions equal to each other and solve for x:
-5/2x - 3 = -3x + 2
-5/2x + 3x = 2 + 3
-5x + 6x = 5
x = 5
Therefore, the exact solution to f(x) = g(x) is x = 5.
A linear function is shown.
f (x)= -5/2x-3
A. create a linear function g (x) such that f (x)=g (x) has exactly one solution
B. what is the exact solution to f (x)=g (x)
A.g(x)=
B.x=
3 answers
what the correct answer
I apologize for the mistake in my previous response. Let's try solving it correctly this time.
A. To create a linear function g(x) such that f(x) = g(x) has exactly one solution, we need to choose a different slope for g(x) that is not equal to -5/2. Let's make the slope of g(x) = -2.
Let g(x) = -2x + 3.
B. To find the exact solution to f(x) = g(x), we set the two functions equal to each other and solve for x:
-5/2x - 3 = -2x + 3
-5/2x + 2x = 3 + 3
(2x - 5/2x) = 6
(4x - 5)/2 = 6
4x - 5 = 12
4x = 17
x = 17/4
Therefore, the exact solution to f(x) = g(x) is x = 17/4.
A. To create a linear function g(x) such that f(x) = g(x) has exactly one solution, we need to choose a different slope for g(x) that is not equal to -5/2. Let's make the slope of g(x) = -2.
Let g(x) = -2x + 3.
B. To find the exact solution to f(x) = g(x), we set the two functions equal to each other and solve for x:
-5/2x - 3 = -2x + 3
-5/2x + 2x = 3 + 3
(2x - 5/2x) = 6
(4x - 5)/2 = 6
4x - 5 = 12
4x = 17
x = 17/4
Therefore, the exact solution to f(x) = g(x) is x = 17/4.